IBC battery aluminum paste and IBC battery

By adding gallium powder to the aluminum slurry of IBC batteries and reducing the content of aluminum, the problem of metal composite formation during the cooling process after sintering is solved, and the effect of improving the open circuit voltage of the battery and photoelectric conversion efficiency is achieved.

CN119852001AActive Publication Date: 2025-04-18DAS SOLAR CO LTD

Patent Information

Application Number
CN202311350589.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18
Estimated Expiration
2043-10-17

AI Technical Summary

Technical Problem

The aluminum paste of existing IBC batteries is prone to form metal composite during cooling after sintering into a positive gate line, resulting in a decrease in the open circuit voltage and photoelectric conversion efficiency of the battery.

Method used

Using an IBC battery aluminum paste containing organic additives, boron powder, aluminum powder, gallium powder, glass powder and organic binder, by adding gallium powder to the aluminum paste, the gallium element quickly drops to the silicon surface during the sintering process, increasing the Ga-Si contact probability, reducing the contact resistance between the slurry and the battery, and reducing the aluminum content to reduce the Al-Si reaction.

Benefits of technology

It effectively improves the open circuit voltage and photoelectric conversion efficiency of the battery, and solves the problem of efficiency reduction caused by metal recombination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852001A_ABST
    Figure CN119852001A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides an IBC battery aluminum paste and an IBC battery, and the IBC battery aluminum paste provided by the embodiment of the invention comprises an organic auxiliary agent, boron powder, aluminum powder, gallium powder, glass powder and an organic binder. The gallium powder is added into the aluminum paste, the gallium element has an etching effect and is high in density, and the gallium element is rapidly reduced to the surface of silicon compared with aluminum in the sintering process, so that the Ga-Si contact probability is increased, the contact resistance of the paste and a battery is reduced, and a high open-circuit voltage can be kept; meanwhile, part of aluminum powder is replaced by gallium, so that the content of aluminum is reduced, the side effect of Al is reduced, the Al-Si reaction is weakened, a formed aluminum-silicon corrosion pit is shallower, the recombination is reduced, the open-circuit voltage and the photoelectric conversion efficiency of the battery are improved, and the service life of the battery is prolonged. Therefore, the problem that the open-circuit voltage and the photoelectric conversion efficiency of a battery piece are reduced due to the fact that metal compounding is easily formed in the cooling process after existing IBC battery aluminum paste is sintered into a positive electrode grid line is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of crystalline silicon solar cell manufacturing, and in particular to an IBC cell silver paste and an IBC cell. Background Art

[0002] The interdigitated back contact (IBC) battery is a new type of battery in which the contact electrodes of the P / N junction, substrate and emitter region are made in an interdigitated shape on the back of the battery. Its core technology is to prepare high-quality p-region and n-region arranged in an interdigitated shape on the back of the battery, and then print aluminum paste connected to the p-region to form the positive electrode grid line, and print silver paste connected to the n-region to form the negative electrode grid line.

[0003] At present, IBC batteries use aluminum paste printed in the P area to form the positive electrode grid line. The aluminum paste can form an alloy with silicon at high temperatures. However, during the cooling process of the battery cell, the aluminum paste can easily diffuse to the PN junction to form a metal composite, resulting in a decrease in the open circuit voltage of the battery cell and a decrease in the photoelectric conversion efficiency. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an IBC battery aluminum paste and an IBC battery to solve the problem that the existing IBC battery aluminum paste is prone to form metal composites during the cooling process after sintering into positive electrode grid lines, resulting in a decrease in the open circuit voltage and photoelectric conversion efficiency of the battery cell.

[0005] In order to solve the above problems, the present invention is achieved through the following technical solutions:

[0006] The present invention provides an IBC battery aluminum paste, wherein the components constituting the aluminum paste include organic additives, boron powder, aluminum powder, gallium powder, glass powder and an organic adhesive.

[0007] Furthermore, in the IBC battery aluminum paste, the mass percentage of the organic additive is 0.2-0.6%; the mass percentage of the boron powder is 0.05-0.1%; the mass percentage of the aluminum powder is 78-82%; the mass percentage of the gallium powder is 0.5-1%; the mass percentage of the glass powder is 1.2-1.5%; and the mass percentage of the organic binder is 18.8-26.05%.

[0008] Furthermore, in the IBC battery aluminum paste, the gallium powder is single-element gallium and / or gallium-aluminum alloy powder.

[0009] Furthermore, in the IBC battery aluminum paste, the boron powder is micron-grade boron powder.

[0010] Furthermore, in the IBC battery aluminum paste, the organic additive includes two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, and lauryl alcohol phosphate.

[0011] Furthermore, in the IBC battery aluminum paste, the aluminum powder includes 85-95% by mass of micron spherical aluminum powder and 5-15% by mass of nano spherical aluminum powder.

[0012] Furthermore, in the IBC battery aluminum paste, the organic binder includes a high molecular polymer resin and an organic solvent;

[0013] The mass fraction of the high molecular weight polymer in the organic binder is 8 to 12%;

[0014] The mass fraction of the organic solvent in the organic binder is 88-92%.

[0015] Furthermore, in the IBC battery aluminum paste, the organic solvent is at least three of benzyl alcohol, diethyl phthalate, pineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

[0016] Furthermore, in the IBC battery aluminum paste, the glass powder includes Bi2O3 with a mass fraction of 20-25%, Al2O3 with a mass fraction of 6-8%, Pb2O5 with a mass fraction of 10-12%, ZnO with a mass fraction of 5-24%, Sb2O5 with a mass fraction of 15-20%, V2O5 with a mass fraction of 5-8%, TiO2 with a mass fraction of 15-22%, and BaO with a mass fraction of 5-20%.

[0017] The present invention further proposes an IBC battery, wherein a plurality of positive electrode grid lines are attached to the back of the IBC battery, and the positive electrode grid lines are prepared from the above-mentioned aluminum paste.

[0018] Compared with the prior art, the embodiments of the present invention have the following advantages:

[0019] In the embodiment of the present invention, the aluminum paste for IBC battery provided comprises organic additives, boron powder, aluminum powder, gallium powder, glass powder and organic binder. By adding gallium powder to the aluminum paste, because gallium element has etching effect and high density, it drops to the silicon surface faster than aluminum during the sintering process, so that the probability of Ga-Si contact is increased, the contact resistance between the paste and the battery is reduced, and a high open circuit voltage can be maintained; at the same time, because gallium is used to replace part of the aluminum powder, the aluminum content is reduced, which is conducive to reducing the side effects of Al, making the Al-Si reaction weaker, and the aluminum-silicon corrosion pit formed is shallower and the composite is reduced, thereby improving the open circuit voltage and photoelectric conversion efficiency of the battery, thus solving the problem that the existing IBC battery aluminum paste is easy to form metal composites during the cooling process after sintering into the positive grid line, resulting in a decrease in the open circuit voltage and photoelectric conversion efficiency of the battery cell.

[0020] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a flow chart of the method for preparing IBC battery aluminum paste provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0022] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0023] An embodiment of the present invention provides an IBC battery aluminum paste, wherein the components constituting the aluminum paste include an organic additive, boron powder, aluminum powder, gallium powder, glass powder and an organic adhesive.

[0024] The IBC battery aluminum paste provided in the embodiment of the present invention is used to form the positive electrode grid line of the IBC battery.

[0025] Among them, aluminum powder is the main component, and aluminum powder mainly replaces the P+ emitter of the battery, while boron powder can diffuse into the silicon for heavy doping during high-temperature sintering, which is beneficial to improve the contact performance of the slurry, reduce the reaction contact surface between aluminum and silicon, and reduce the contact resistivity between the positive electrode grid and the battery, thereby improving the filling of the battery and the efficiency of the battery;

[0026] Among them, the gallium element in the gallium powder has an etching effect and a high density. During the sintering process, it drops to the silicon surface faster than aluminum, which increases the probability of Ga-Si contact, reduces the contact resistance between the slurry and the battery, and can maintain a high open circuit voltage. At the same time, because gallium is used to replace part of the aluminum powder, the aluminum content is reduced, which is conducive to reducing the side effects of Al, making the Al-Si reaction weaker, and the aluminum-silicon corrosion pits formed are shallower and the recombination is reduced, thereby improving the open circuit voltage and photoelectric conversion efficiency of the battery.

[0027] Among them, glass powder is an inorganic adhesive, which will melt into liquid under high temperature conditions and condense when cooled to play a bonding role; organic adhesive can ensure the overall bonding effect; organic additives can reduce the overall viscosity of silver paste.

[0028] Therefore, the aluminum paste provided in the embodiment of the present invention can solve the problem that the aluminum paste of the existing IBC battery easily forms metal composites during the cooling process after sintering into the positive electrode grid line, resulting in a decrease in the open circuit voltage and photoelectric conversion efficiency of the battery cell.

[0029] Optionally, in one embodiment, in the above-mentioned aluminum paste, the mass percentage of organic additive is 0.2-0.6%, the mass percentage of boron powder is 0.05-0.1%, the mass percentage of aluminum powder is 72-78%, the mass percentage of gallium powder is 0.5-1%, the mass percentage of glass powder is 1.2-1.5%, and the mass percentage of organic binder is 18.8-26.05%.

[0030] For example, in the aluminum paste, the mass fractions of the organic additive, boron powder, aluminum powder, gallium powder, glass powder and organic binder are 0.5%, 0.05%, 76%, 0.5%, 1.5% and 21.45% respectively.

[0031] For example, in the aluminum paste, the mass fractions of the organic additive, boron powder, aluminum powder, gallium powder, glass powder and organic binder are 0.5%, 0.08%, 76%, 0.8%, 1.3% and 21.32% respectively.

[0032] For example, in the aluminum paste, the mass fractions of the organic additive, boron powder, aluminum powder, gallium powder, glass powder and organic binder are 0.2%, 0.05%, 72%, 0.5%, 1.2% and 26.05% respectively.

[0033] For example, in the aluminum paste, the mass fractions of the organic additive, boron powder, aluminum powder, gallium powder, glass powder and organic binder are 0.6%, 0.1%, 78%, 1%, 1.5% and 18.8% respectively.

[0034] Optionally, in one embodiment, the boron powder comprises elemental boron.

[0035] Optionally, in a specific embodiment, the boron powder includes micron-sized elemental boron. By adding the micron-sized elemental boron, the boron powder can quickly diffuse into the silicon for heavy doping during high-temperature sintering, which is beneficial to improving the contact performance of the slurry.

[0036] Optionally, in a specific embodiment, the boron powder is micron-grade boron powder with a purity of 3 9s.

[0037] Optionally, in one embodiment, the gallium powder comprises single element gallium.

[0038] Optionally, in a specific embodiment, the gallium powder includes micron-sized single-element gallium. By adding the micron-sized single-element gallium, the gallium powder can quickly diffuse into the silicon during high-temperature sintering, thereby reducing the contact resistance between the slurry and the battery.

[0039] Optionally, in a specific embodiment, the gallium powder is micron-grade gallium powder with a purity of 2 9.

[0040] Optionally, in another embodiment, the gallium powder comprises a gallium-aluminum alloy. By adding the micron-sized gallium-aluminum alloy powder, the aluminum paste can quickly form a good gallium-silicon alloy with silicon under a relatively low sintering temperature condition.

[0041] Optionally, in one embodiment, the aluminum powder includes 85-95% by mass of micron-sized spherical aluminum powder and 5-15% by mass of nano-sized spherical aluminum powder. Since there are gaps between the micron-sized aluminum powders, the nano-sized spherical aluminum powder can just fill and penetrate into the gaps between the micron-sized aluminum powders.

[0042] Optionally, in a specific embodiment, the aluminum powder includes micron-sized spherical aluminum powder with a purity of 3 9s and a mass fraction of 85-95%, and nano-sized spherical aluminum powder with a purity of 3 9s and a mass fraction of 5-15%.

[0043] Optionally, in one embodiment, the above-mentioned organic auxiliary agent includes two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, lauryl alcohol phosphate, Digo 655, BYK110, and BYK105.

[0044] In the aluminum paste provided in the embodiment of the present invention, the above-mentioned organic binder includes a high molecular polymer resin and an organic solvent; wherein the high molecular polymer resin is dissolved in the organic solvent, so that the organic solvent can be used as an organic binder, that is, the paste plays a role of bonding powder after drying.

[0045] Optionally, in one embodiment, the mass fraction of the high molecular weight polymer in the organic binder is 8-12%; the mass fraction of the organic solvent in the organic binder is 88-92%.

[0046] Optionally, in one embodiment, the high molecular weight polymer is one or more of ethyl cellulose-N20, ethyl cellulose N-50, and ethyl cellulose-N100;

[0047] The organic solvent comprises at least three of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

[0048] Optionally, in one embodiment, the glass powder includes, by mass, 20-25% Bi2O3, 6-8% Al2O3, 10-12% Pb2O5, 5-24% ZnO, 15-20% Sb2O5, 5-8% V2O5, 15-22% TiO2, and 5-20% BaO, and the D50 of the glass powder is 1.2-1.8μm. If D50 is less than 1.2μm, the glass activity is too large, and if D50 is greater than 1.8μm, the glass activity is too small.

[0049] Among them, Bi2O3 is the main network structure, ZnO can break the network structure and promote glass crystallization, Sb2O5 is used to clarify and uniform the glass liquid; Al2O3 can adjust the stability of the glass and increase the viscosity; Pb2O5 reacts with silicon nitride to generate lead, nitrogen and silicon dioxide; V2O5 and TiO2 can assist Pb2O5 and silicon nitride in the reaction; BaO is used for local crystallization.

[0050] For example, the glass powder includes, by mass, 22% Bi2O3, 6% Al2O3, 12% Pb2O5, 10% ZnO, 18% Sb2O5, 7% V2O5, 15% TiO2, and 10% BaO.

[0051] For example, the glass powder includes, by mass, 20% Bi2O3, 8% Al2O3, 10% Pb2O5, 5% ZnO, 20% Sb2O5, 5% V2O5, 22% TiO2, and 10% BaO.

[0052] For example, the glass powder includes, by mass, 20% Bi2O3, 6% Al2O3, 10% Pb2O5, 24% ZnO, 15% Sb2O5, 5% V2O5, 15% TiO2, and 5% BaO.

[0053] The present invention also provides a method for preparing an IBC battery aluminum paste, wherein: Figure 1 As shown, it includes steps 101 to 102:

[0054] Step 101, mixing aluminum powder, boron powder, gallium powder, organic binder and glass powder to obtain a mixture;

[0055] Step 102: Grind the mixture and add an organic additive to obtain aluminum paste for forming positive grid lines of an IBC battery.

[0056] In the above step 101, 72-78% of aluminum powder, 0.05-0.1% of boron powder, 0.5-1% of gallium powder, 18.8-26.05% of organic binder, and 1.2-1.5% of glass powder accounting for the total mass of the raw materials are weighed and mixed, and dispersed by a disperser to obtain the above mixture.

[0057] Optionally, in one embodiment, in the above step 101, the organic binder and boron powder are first mixed and dispersed using a disperser, and then aluminum powder and glass powder are added, dispersed again using a disperser, and then ground to obtain the above mixture.

[0058] In the above step 102, the above mixture is ground and then an organic additive accounting for 0.2-0.6% of the total mass of the raw materials is added, and after high-speed dispersion, an aluminum paste for forming the positive grid line of an IBC battery is obtained.

[0059] In the embodiment of the present invention, gallium powder is added to the aluminum paste. Since gallium element has an etching effect and a high density, it drops to the silicon surface faster than aluminum during the sintering process, thereby increasing the Ga-Si contact probability, reducing the contact resistance between the slurry and the battery, and maintaining a relatively high open circuit voltage. At the same time, since gallium is used to replace part of the aluminum powder, the aluminum content is reduced, which is beneficial to reducing the side effects of Al, weakening the Al-Si reaction, and forming shallow aluminum-silicon corrosion pits and reducing the recombination, thereby improving the open circuit voltage and photoelectric conversion efficiency of the battery. This solves the problem that the aluminum paste of the existing IBC battery is prone to form metal composites during the cooling process after sintering to form the positive electrode grid line, resulting in a decrease in the open circuit voltage and photoelectric conversion efficiency of the battery cell.

[0060] Optionally, in the preparation method provided in the embodiment of the present invention, the gallium powder is single-element gallium and / or gallium-aluminum alloy powder.

[0061] Optionally, in the preparation method provided in an embodiment of the present invention, the boron powder is micron-grade boron powder.

[0062] Optionally, in the preparation method provided in the embodiment of the present invention, the organic auxiliary agent includes two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, and lauryl alcohol phosphate.

[0063] Optionally, in the preparation method provided in an embodiment of the present invention, the aluminum powder includes 85-95% by mass of micron spherical aluminum powder and 5-15% by mass of nano spherical aluminum powder; in the above step 101, the organic adhesive, nano aluminum powder, boron powder and gallium powder are first mixed and dispersed using a disperser, and then the micron aluminum powder and glass powder are added, dispersed again using a disperser, and then ground to obtain the above mixture.

[0064] Optionally, in the preparation method provided in the embodiment of the present invention, the organic binder comprises a high molecular polymer resin and an organic solvent;

[0065] The mass fraction of the high molecular weight polymer in the organic binder is 8 to 12%;

[0066] The mass fraction of the organic solvent in the organic binder is 88-92%.

[0067] Optionally, in the preparation method provided in an embodiment of the present invention, the organic solvent is at least three of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

[0068] Optionally, in the preparation method provided in an embodiment of the present invention, the glass powder includes Bi2O3 with a mass fraction of 20-25%, Al2O3 with a mass fraction of 6-8%, Pb2O5 with a mass fraction of 10-12%, ZnO with a mass fraction of 5-24%, Sb2O5 with a mass fraction of 15-20%, V2O5 with a mass fraction of 5-8%, TiO2 with a mass fraction of 15-22%, and BaO with a mass fraction of 5-20%.

[0069] The present invention also provides an IBC battery, wherein a plurality of positive electrode grid lines are attached to the back of the IBC battery, and the positive electrode grid lines are prepared from the above-mentioned aluminum paste.

[0070] Among them, the above-mentioned IBC battery can be a P-type IBC battery.

[0071] The steps of using the aluminum paste provided in the embodiment of the present invention to make a P-type IBC battery are as follows:

[0072] (1) After sequentially forming a silicon oxide layer and a phosphorus-doped polysilicon layer on the back of a P-type silicon wafer, a passivation film layer and an anti-reflection film layer are formed on both sides of the silicon wafer;

[0073] (2) Laser grooving is performed on the back of the silicon wafer to form interdigitated p-type doped regions and n-type native silicon regions;

[0074] (3) Printing aluminum paste in the laser grooved area to form the positive electrode grid line, and printing silver paste in the n-type doped area to form the negative electrode grid line, to produce a P-type IBC battery.

[0075] The present invention is described in detail below by way of examples.

[0076] Example 1

[0077] (1) providing aluminum paste a1: the aluminum paste a1 is composed of 0.5 parts of an organic additive, 0.05 parts of boron powder, 76 parts of aluminum powder, 0.5 parts of gallium powder, 21.45 parts of an organic binder and 1.5 parts of glass powder, by weight;

[0078] Among them, the above-mentioned organic additives are lauryl alcohol phosphate and BYK110; the boron powder is a micron-level elemental boron with a purity of 3 9s; the aluminum powder includes a micron-level spherical aluminum powder with a purity of 3 9s and a mass fraction of 90%, and a nano-spherical aluminum powder with a purity of 3 9s and a mass fraction of 10%; the gallium powder is a micron-level elemental gallium with a purity of 2 9s; the organic binder includes ethyl cellulose-N100 with a mass fraction of 10% and an organic solvent with a mass fraction of 90%, and the organic solvent is composed of benzyl alcohol, pine oil, butyl carbitol, butyl carbitol acetate and Span 85; the glass powder is obtained by sintering and crushing 22% Bi2O3, 6% Al2O3, 12% Pb2O5, 10% ZnO, 18% Sb2O5, 7% V2O5, 15% TiO2, and 10% BaO with a mass percentage, and its D50 is 1.2-1.8μm.

[0079] (2) The aluminum paste is screen-printed on a single crystal P-type silicon wafer with a size of 182 mm × 182 mm to form an aluminum fine grid, which is then sintered in a sintering furnace with a peak sintering temperature of 768°C. After sintering, a P-type IBC battery is obtained.

[0080] The electrical performance data of the battery was tested, and the results showed that the open circuit voltage was 0.7241V, the short circuit current was 13.915mA, the fill factor was 83.4%, and the photoelectric conversion efficiency was 25.45%.

[0081] Example 2

[0082] (1) providing aluminum paste a2: aluminum paste a1 is composed of 0.5 parts of organic additive, 0.08 parts of boron powder, 76 parts of aluminum powder, 0.8 parts of gallium powder, 21.32 parts of organic binder and 1.3 parts of glass powder, by weight;

[0083] Among them, the above-mentioned organic additives are lauryl alcohol phosphate and BYK110; the boron powder is a micron-level elemental boron with a purity of 3 9s; the aluminum powder includes a micron-level spherical aluminum powder with a purity of 3 9s and a mass fraction of 92%, and a nano-spherical aluminum powder with a purity of 3 9s and a mass fraction of 8%; the gallium powder is a micron-level elemental gallium with a purity of 2 9s; the organic binder includes ethyl cellulose-N100 with a mass fraction of 10% and an organic solvent with a mass fraction of 90%, and the organic solvent is composed of benzyl alcohol, pine oil, butyl carbitol, butyl carbitol acetate and Span 85; the glass powder is obtained by sintering and crushing 22% Bi2O3, 6% Al2O3, 12% Pb2O5, 10% ZnO, 18% Sb2O5, 7% V2O5, 15% TiO2, and 10% BaO with a mass percentage, and its D50 is 1.2-1.8μm.

[0084] (2) The aluminum paste is screen-printed on a single crystal P-type silicon wafer with a size of 182 mm × 182 mm to form an aluminum fine grid, which is then sintered in a sintering furnace with a peak sintering temperature of 768°C. After sintering, a P-type IBC battery is obtained.

[0085] The electrical performance data of the battery was tested, and the results showed that the open circuit voltage was 0.7251V, the short circuit current was 13.935mA, the fill factor was 83.35%, and the photoelectric conversion efficiency was 25.51%.

[0086] Example 3

[0087] (1) providing aluminum paste a3: in parts by mass, the aluminum paste a1 is composed of 0.2 parts of an organic additive, 0.05 parts of boron powder, 72 parts of aluminum powder, 0.5 parts of gallium powder, 26.05 parts of an organic binder and 1.2 parts of glass powder;

[0088] Among them, the above-mentioned organic additives are lauryl alcohol phosphate and BYK110; the boron powder is a micron-level elemental boron with a purity of 3 9s; the aluminum powder includes a micron-level spherical aluminum powder with a purity of 3 9s and a mass fraction of 90%, and a nano-spherical aluminum powder with a purity of 3 9s and a mass fraction of 10%; the gallium powder is a micron-level elemental gallium with a purity of 2 9s; the organic binder includes ethyl cellulose-N100 with a mass fraction of 10% and an organic solvent with a mass fraction of 90%, and the organic solvent is composed of benzyl alcohol, pine oil, butyl carbitol, butyl carbitol acetate and Span 85; the glass powder is obtained by sintering and crushing 22% Bi2O3, 6% Al2O3, 12% Pb2O5, 10% ZnO, 18% Sb2O5, 7% V2O5, 15% TiO2, and 10% BaO with a mass percentage, and its D50 is 1.2-1.8μm.

[0089] (2) The aluminum paste is screen-printed on a single crystal P-type silicon wafer with a size of 182 mm × 182 mm to form an aluminum fine grid, which is then sintered in a sintering furnace with a peak sintering temperature of 768°C. After sintering, a P-type IBC battery is obtained.

[0090] The electrical performance data of the battery was tested, and the results showed that the open circuit voltage was 0.7235V, the short circuit current was 13.918mA, the fill factor was 83.21%, and the photoelectric conversion efficiency was 25.379%.

[0091] Example 4

[0092] (1) providing aluminum paste a4: in parts by mass, aluminum paste a1 is composed of 0.6 parts of an organic additive, 0.1 parts of boron powder, 78 parts of aluminum powder, 1 part of gallium powder, 18.8 parts of an organic binder and 1.5 parts of glass powder;

[0093] Among them, the above-mentioned organic additives are lauryl alcohol phosphate and BYK110; the boron powder is a micron-grade elemental boron with a purity of 3 9s; the aluminum powder includes a micron-grade spherical aluminum powder with a purity of 3 9s and a mass fraction of 90%, and a nano-spherical aluminum powder with a purity of 3 9s and a mass fraction of 10%; the gallium powder is a micron-grade gallium-aluminum alloy with a purity of 2 9s; the organic binder includes ethyl cellulose-N100 with a mass fraction of 10% and an organic solvent with a mass fraction of 90%, and the organic solvent is composed of benzyl alcohol, pine oil, butyl carbitol, butyl carbitol acetate and Span 85; the glass powder is obtained by sintering and crushing 22% Bi2O3, 6% Al2O3, 12% Pb2O5, 10% ZnO, 18% Sb2O5, 7% V2O5, 15% TiO2, and 10% BaO with a mass percentage, and its D50 is 1.2-1.8μm.

[0094] (2) The aluminum paste is screen-printed on a single crystal P-type silicon wafer with a size of 182 mm × 182 mm to form an aluminum fine grid, which is then sintered in a sintering furnace with a peak sintering temperature of 768°C. After sintering, a P-type IBC battery is obtained.

[0095] The electrical performance data of the battery was tested, and the results showed that the open circuit voltage was 0.7255V, the short circuit current was 13.941mA, the fill factor was 83.382%, and the photoelectric conversion efficiency was 25.544%.

[0096] Example 5

[0097] (1) providing aluminum paste a5: in parts by mass, the aluminum paste a1 is composed of 0.5 parts of an organic additive, 0.08 parts of boron powder, 76 parts of aluminum powder, 0.8 parts of gallium powder, 21.32 parts of an organic binder and 1.3 parts of glass powder;

[0098] Among them, the above-mentioned organic additives are lauryl alcohol phosphate and BYK110; the boron powder is a micron-level elemental boron with a purity of 3 9s; the aluminum powder includes a micron-level spherical aluminum powder with a purity of 3 9s and a mass fraction of 90%, and a nano-spherical aluminum powder with a purity of 3 9s and a mass fraction of 10%; the gallium powder is a micron-level elemental gallium with a purity of 2 9s; the organic binder includes ethyl cellulose-N100 with a mass fraction of 10% and an organic solvent with a mass fraction of 90%, and the organic solvent is composed of benzyl alcohol, pine oil, butyl carbitol, butyl carbitol acetate and Span 85; the glass powder is obtained by sintering and crushing 22% Bi2O3, 6% Al2O3, 12% Pb2O5, 10% ZnO, 18% Sb2O5, 7% V2O5, 15% TiO2, and 10% BaO with a mass percentage, and its D50 is 1.2-1.8μm.

[0099] (2) The aluminum paste is screen-printed on a single crystal N-type silicon wafer with a size of 182 mm × 182 mm to form an aluminum fine grid, which is then sintered in a sintering furnace with a peak sintering temperature of 774°C. After sintering, an N-type IBC battery is obtained.

[0100] The electrical performance data of the battery was tested, and the results showed that the open circuit voltage was 0.7261V, the short circuit current was 13.954mA, the fill factor was 83.345%, and the photoelectric conversion efficiency was 25.577%.

[0101] Comparative Example 1

[0102] (1) providing aluminum paste b1: in parts by mass, the aluminum paste a1 is composed of 0.5 parts of an organic additive, 0.05 parts of boron powder, 76.5 parts of aluminum powder, 21.45 parts of an organic binder and 1.5 parts of glass powder;

[0103] Among them, the above-mentioned organic additives are lauryl alcohol phosphate and BYK110; the boron powder is micron-grade elemental boron with a purity of 3 9s; the aluminum powder includes micron-grade spherical aluminum powder with a purity of 3 9s and a mass fraction of 90%, and nano-spherical aluminum powder with a purity of 3 9s and a mass fraction of 10%; the organic binder includes ethyl cellulose-N100 with a mass fraction of 10% and an organic solvent with a mass fraction of 90%, and the organic solvent is composed of benzyl alcohol, pine oil, butyl carbitol, butyl carbitol acetate and Span 85; the glass powder is obtained by sintering and crushing 22% Bi2O3, 6% Al2O3, 12% Pb2O5, 10% ZnO, 18% Sb2O5, 7% V2O5, 15% TiO2, and 10% BaO with a mass percentage, and its D50 is 1.2-1.8μm.

[0104] (2) The aluminum paste is screen-printed with a 360-mesh screen onto a laser-grooved single-crystal P-type silicon wafer with a size of 182 mm × 182 mm to form an aluminum fine grid, which is then sintered in a sintering furnace at a peak sintering temperature of 768°C to obtain a P-type IBC battery.

[0105] The electrical performance data of the battery was tested, and the results showed that the open circuit voltage was 0.7217V, the short circuit current was 13.945mA, the fill factor was 83.185%, and the photoelectric conversion efficiency was 25.357%.

[0106] Comparative Example 2

[0107] (1) providing aluminum paste b2: aluminum paste a1 is composed of 0.8 parts of organic additive, 0.1 parts of boron powder, 76.5 parts of aluminum powder, 21.1 parts of organic binder and 1.5 parts of glass powder, by weight;

[0108] Among them, the above-mentioned organic additives are lauryl alcohol phosphate and BYK110; the boron powder is micron-grade elemental boron with a purity of 3 9s; the aluminum powder includes micron-grade spherical aluminum powder with a purity of 3 9s and a mass fraction of 93%, and nano-spherical aluminum powder with a purity of 3 9s and a mass fraction of 7%; the organic binder includes ethyl cellulose-N100 with a mass fraction of 8% and an organic solvent with a mass fraction of 92%, and the organic solvent is composed of benzyl alcohol, pine oil, butyl carbitol, butyl carbitol acetate and Span 85; the glass powder is obtained by sintering and crushing 20% ​​SiO2, 8% Al2O3, 12% Pb2O5, 12% ZnO, 20% V2O5, 6% B2O3, and 22% TeO2 with a mass percentage, and its D50 is 1.5-1.8μm.

[0109] (2) The aluminum paste is screen-printed with a 360-mesh screen onto a laser-grooved single-crystal P-type silicon wafer with a size of 182 mm × 182 mm to form an aluminum fine grid, which is then sintered in a sintering furnace at a peak sintering temperature of 788° C. After sintering, a P-type IBC battery is obtained.

[0110] The electrical performance data of the battery was tested, and the results showed that the open circuit voltage was 0.7208V, the short circuit current was 13.931mA, the fill factor was 83.187%, and the photoelectric conversion efficiency was 25.301%.

[0111] By comparing Examples 1 to 5 and Comparative Examples 1 and 2, it can be seen that the embodiments of the present invention can effectively improve the open circuit voltage and photoelectric conversion efficiency of the battery.

[0112] In summary, in this embodiment, gallium powder is added to the aluminum paste. Since gallium element has an etching effect and a high density, it drops to the silicon surface faster than aluminum during the sintering process, thereby increasing the Ga-Si contact probability, reducing the contact resistance between the slurry and the battery, and maintaining a relatively high open circuit voltage. At the same time, since gallium is used to replace part of the aluminum powder, the aluminum content is reduced, which is beneficial to reducing the side effects of Al, weakening the Al-Si reaction, and forming shallow aluminum-silicon corrosion pits and reducing the recombination, thereby improving the open circuit voltage and photoelectric conversion efficiency of the battery. This solves the problem that the aluminum paste of the existing IBC battery is prone to form metal composites during the cooling process after sintering into the positive electrode grid line, resulting in a decrease in the open circuit voltage and photoelectric conversion efficiency of the battery cell.

[0113] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.

[0114] The above is a detailed introduction to an IBC battery aluminum paste and an IBC battery provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. An IBC battery aluminum paste, characterized in that: The components constituting the aluminum paste include organic additives, boron powder, aluminum powder, gallium powder, glass powder and organic binder.

2. The IBC battery aluminum paste according to claim 1, characterized in that: The mass percentage of the organic additive is 0.2-0.6%; the mass percentage of the boron powder is 0.05-0.1%; the mass percentage of the aluminum powder is 72-78%; the mass percentage of the gallium powder is 0.5-1%; the mass percentage of the glass powder is 1.2-1.5%; and the mass percentage of the organic binder is 18.8-26.05%.

3. The IBC battery aluminum paste according to claim 1, characterized in that: The gallium powder is single-element gallium and / or gallium-aluminum alloy powder.

4. The aluminum paste according to claim 1, characterized in that The boron powder is micron-grade boron powder.

5. The aluminum paste according to claim 1, characterized in that: The organic auxiliary agent includes two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent and lauryl alcohol phosphate.

6. The aluminum paste according to claim 1, characterized in that: The aluminum powder comprises 85-95% by mass of micron spherical aluminum powder and 5-15% by mass of nanometer spherical aluminum powder.

7. The aluminum paste according to claim 1, characterized in that: The organic binder includes a high molecular polymer resin and an organic solvent; The mass fraction of the high molecular weight polymer in the organic binder is 8 to 12%; The mass fraction of the organic solvent in the organic binder is 88-92%.

8. The aluminum paste according to claim 7, characterized in that: The organic solvent comprises at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

9. The aluminum paste according to claim 1, characterized in that: The glass powder includes Bi2O3 with a mass fraction of 20-25%, Al2O3 with a mass fraction of 6-8%, Pb2O5 with a mass fraction of 10-12%, ZnO with a mass fraction of 5-24%, Sb2O5 with a mass fraction of 15-20%, V2O5 with a mass fraction of 5-8%, TiO2 with a mass fraction of 15-22%, and BaO with a mass fraction of 5-20%.

10. An IBC battery, characterized in that: A plurality of positive electrode grid lines are attached to the back of the IBC battery, and the positive electrode grid lines are prepared from the aluminum paste described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Aluminum conductive paste for silicon solar cell back surface field and preparation method thereof

    CN101621082A

  • Aluminum pulp composition of crystal silicon solar cell and preparation method thereof

    CN101728439A

  • Sizing agent for Al-BSF (Al-back surface field) of silicon solar cell and preparation method thereof

    CN102254587A

  • Solar cell backside aluminum paste powder adaptable to high sheet resistance and shallow junction

    CN103000247A

  • Aluminium paste for solar cell, and application of aluminium paste

    CN107342116A

Cited By

  • Battery piece and preparation method thereof, laminated battery and photovoltaic module

    CN122337725A